2010
DOI: 10.1111/j.1530-0277.2010.01162.x
|View full text |Cite
|
Sign up to set email alerts
|

Verbal and Nonverbal Memory in Adults Prenatally Exposed to Alcohol

Abstract: Background Neurocognitive effects of prenatal alcohol exposure in adulthood are not well documented. Questions persist regarding the extent to which there are specific, measurable effects beyond those associated with global ability deficits, whether individuals without the full fetal alcohol syndrome (FAS) demonstrate alcohol-related cognitive impairments and whether observed memory effects are specific to a particular modality, that is, verbal versus visual/spatial domains. Methods In this study, verbal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 38 publications
3
56
0
1
Order By: Relevance
“…Deficits in organizational or metamemory strategies for encoding and retrieving information have been identified among children with PAE [37]. However, strategies to support memory can be helpful and retrieval or retention of learned material may be less affected than encoding [38].…”
Section: Memory Deficitsmentioning
confidence: 98%
“…Deficits in organizational or metamemory strategies for encoding and retrieving information have been identified among children with PAE [37]. However, strategies to support memory can be helpful and retrieval or retention of learned material may be less affected than encoding [38].…”
Section: Memory Deficitsmentioning
confidence: 98%
“…Case accounts of individuals with FASD have shown that postsecondary education and consistent employment outcomes are possible (e.g., Boyle Street Education Centre 2007;Community Living British Columbia 2011;Erb 2015). However, the literature is generally reflective of lower expectations of adult development for youth with FASD, noting that memory challenges and social challenges contribute to learning and health difficulties for many (Coles et al 2010;Denys et al 2011;O'Connor and Paley 2009). However, educational and occupational opportunities can be facilitated through community-based initiatives that inform adults and their caregivers about appropriate programs (Grant et al 2004;Denys et al 2011).…”
Section: Upport Servicesmentioning
confidence: 99%
“…In general, extensive and diffuse alcohol effects result in significant disabilities that require intensive and longerterm support (Fagerlund et al 2011). It has been noted, for example, that memory problems persist from childhood into young adulthood (Coles et al 2010) and that children with FASD will have elevated rates of mental health problems as young adults (Denys et al 2011;O'Connor and Paley 2009). Anecdotally, however, as reflected in several case accounts, a high quality of life is possible (e.g., Boyle Street Education Centre 2007; Community Living British Columbia 2011;Erb 2015).…”
Section: Introductionmentioning
confidence: 99%
“…FASD children and adults have been found to commonly have deficits in IQ , attention and executive control (e.g., planning and problem-solving ability, impulse control; Brown et al, 1991;Coles et al, 1997;Connor, Streissguth, Sampson, Bookstein, & Barr, 1999), speed of information processing (Burden et al, 2005;Jacobson, 1998), mathematics and number processing (Goldschmidt, Richardson, Stoffer, Geva, & Day, 1996;Mattson, Riley, Gramling, Delis, & Jones, 1998), memory (Coles, Lynch, Kable, Johnson, & Goldstein, 2010;Uecker & Nadel, 1996), and social information processing (McGee, Bjorkquist, Price, .…”
Section: Introductionmentioning
confidence: 99%